Human-Centric Functional Modeling of Biocomputers - Williams, Andy (My University, 2021)
This paper explores how the technique of Human-Centric Functional Modeling might potentially be used to represent a broad subset of proposed implementations of biocomputing with anywhere from narrow to general problem-solving ability within a given domain, or across multiple domains, and how such functional models might be implemented by libraries of biological computing mechanisms. This paper also explores the insights to be gained from modeling biocomputers this way, and how Human-Centric Functional Modeling might significantly accelerate research and increase the impact of research in biocomputing through significantly increasing capacity for reuse of both biocomputing hardware and software.
Keywords: biocomputing; General Collective Intelligence; Human-Centric Functional Modelling